The Influence of Training Using Audio Visual and Image Media in Futsal Extracurricular Activities at SMAN 4 Tanjungpinang - Rizki Kurniawan; Bafirman Bafirman; Umar Umar; Muhamad Sazeli Rifki (JETL (Journal of Education, Teaching and Learning), 2025)
This study investigates the effectiveness of training using audio visual and image media in improving shooting skills using the inside of the foot in extracurricular futsal games at SMAN 4 Tanjungpinang. Many students lack understanding of the correct techniques for kicking, especially in penalty situations. One contributing factor is the monotonous and less varied training methods used during extracurricular sessions. This research adopts a quantitative approach with a pretest-posttest group design. The sample consisted of 30 students divided into two equal groups: one trained using audio visual media, and the other with image media. Each group received specific training focused on shooting with the inside of the foot. Pretest and posttest assessments were conducted to measure shooting performance. The results showed that: (1) there was a significant effect of training using audio visual media on shooting results, with a significance value of 0.000 (< 0.05), indicating Ho is rejected; (2) training using image media also had a significant effect on shooting results, with a significance value of 0.000 (< 0.05), indicating Ho is rejected; and (3) there was no significant difference in effectiveness between the two media, with an Independent Sample Test significance value of 0.447 (> 0.05), indicating Ho is accepted. The study concludes that both audio visual and image media are effective in improving shooting skills using the inside of the foot, although neither method proved significantly superior.